Polyurethane Foams from Liquefied Eucalyptus globulus Branches - Domingos, Idalina J. (2019)
Currently, polyurethane (PU) production is completely dependent upon fossil oil, as the two primary reagents necessary for PU production, polyol and isocyanate, are derived from fossil fuels. Eucalyptus branches are waste products for most forest management companies. In this work, polyols obtained by the liquefaction of eucalyptus branches were used for foam production. The influence of the isocyanate, catalyst, surfactant, and blowing agent contents on the foam properties was studied. Overall the amount of each chemical used in the production of PU foams had a noticeable effect on the density and compressive properties. The amount of water (blowing agent) had the strongest effect and decreased the density and compressive properties because of higher foam expansion. The other chemicals increased or decreased the density and compressive stress depending on the amount used. The density of the produced foams ranged from 36 kg/m3 to 108 kg/m3, the compressive stress ranged from 15 kPa to 149 kPa, and the Young’s modulus ranged from 64 kPa to 2100 kPa. The results showed that it is possible to convert these forest residues into PU foams with properties somewhat similar to those of commercial foams, although with a lower compressive strength.